"Open, Honest, Passionate and with Some Humor": Understanding Trust Building between British Muslims and the Wider Community. Issue 3 (3rd July 2021) - Latif, Asam; Gulzar, Nargis; Vaughan, Aliya; Khan, Farah; Hussain, Musharraf
Abstract: The "Trust Building" initiative, launched in the United Kingdom in April 2016, aimed to dispel myths about Islam and build trust between Muslims and the wider community. This community-led initiative involved trained Trust Building "Ambassadors" delivering workshops at places of work and other community settings to talk about Islam and facilitate open dialogue. Previously, the project reported trust among participants had significantly improved, but the reasons for this were not explored. In this paper, we unpack how and why trust was being built. Providing a forum that permits open dialogue between Muslims and the wider community allowed opportunities for stories and experiences to be shared, enabling negative stereotypes to be uncovered and addressed, and for mutual values to be recognised. With negative media portrayal and rise in hate crime towards minorities, this research is a promising model that has important implications to address the trust deficit seen within our society.